Hubungan Self-Compassion dengan Orientasi Masa Depan Mahasiswa Angkatan 2017 Program Studi Manajemen UNIBI - Febriyani, Devi; Hastuti, Evi Srinur; Khairina, Nida (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2021)
Students are in the age where they start exploring their careers and planning for their future. Internal and external factors can influence it, so the future needs to be prepared comprehensively. This is known as future orientation (OMD). Healthy self-acceptance factors (self-compassion) also play an important role in an individual's readiness to face their future. However, this isn’t parallel with the facts around us. Many students don’t accept their own condition, and often labelling themselves with something negative. Therefore, it’s necessary to conduct a study about relationship between self-compassion and future orientation. This study aims to determine the relationship between self-compassion and future orientation in the student of 2017 year of UNIBI Management Study Program. Using quantitative research methods, this study was conducted on 69 students. The measuring instruments is Self-Compassion Scale which adapted into Indonesian, as well as the Future Orientation measuring instrument constructed from Nurmi's theory. Product Moment analysis was used to obtain accurate results. Based on the results of the analysis, data was obtained that there is a positive relationship between self-compassion and future orientation with a correlation value of 0.652. So the more compassionate students are, the more focused their future orientation will be